Step-by-step of ultrasound-guided core-needle biopsy of the breast: review and technique - Rocha,Rafael Dahmer (2013)
Ultrasound-guided core-needle biopsy has high sensitivity in the diagnosis of breast cancer. The present study is aimed at detailing the main steps of such procedure, including indications, advantages, limitations, follow-up and description of the technique, besides presenting a checklist including the critical steps required for an appropriate practice of the technique. In the recent years, an increasing number of patients have required breast biopsy, indicating the necessity of a proportional increase in the number of skilled professionals to carry out the procedures and histological diagnoses. A multidisciplinary approach involving the tripod clinical practice-radiology-pathology is responsible for the highest rate of accuracy of the technique and must always be adopted.